123 Effects of Different Feeding Regimes During Wean-to-estrus Interval on Sow Reproductive Performance. (7th May 2021) - Lu, Ning; Popa, Ghenadie; Wang, Ruiming; Vier, Carine M; Navales, Ron A; Cast, Wayne R; Orlando, Uislei A
Abstract: A total of 386 mixed parity sows were used to evaluate the effects of different feeding regimes during the wean-to-estrus interval (WEI) on reproductive performance. At weaning, sows were blocked by genetic line (PIC Yorkshire and Camborough, Hendersonville, TN), parity category (Parity 1 and 4+), weaning visual body condition scores (BCS), and allotted to one of two treatments in a randomized complete block design. The number of weaned piglets of the previous lactation was balanced across treatments. Sows with BCS of 1 at weaning (based on a 3-point scale BCS system) were excluded from the study. A corn-soybean meal-soy hull-wheat bran-based gestation diet with 2.97 Mcal of ME/kg and 0.70% SID lysine was fed in the study. Treatments included two feeding regimes during WEI: T1) feed allowance of 4.5 kg/d with 200 g/day of top-dressed glucose; T2) feed allowance of 3 kg/day. Sows from T1 received two 2.25-kg meals at 0800 and 1630 with 200 g of glucose top-dressed in the morning meal. Sows from T2 received one 3-kg meal at 0800. Experimental data were analyzed using generalized linear mixed models with the GLIMMIX procedure of SAS and sow as the experimental unit. There was no evidence for differences between treatments on WEI (T1: 4.48 days; T2: 4.53 days; P = 0.60); percentage of sows that returned to estrus within 7 days post-weaning (T1: 86.01%; T2: 89.64%; P = 0.47); or conception rate at day 35 of the subsequent gestation (T1: 95.87%; T2: 98.50%; P = 0.44). In conclusion, feeding 4.5 kg of gestation diet and 200 g of glucose per day during WEI did not improve return to estrus or conception rate compared to feeding 3 kg of gestation diet per day for weaned sows with BCS greater than 1 on a 3-point scale.